SMT of German Patents at WIPO: Decompounding and Verb Structure Pre-reordering - Junczys-Dowmunt, Marcin; Pouliquen, Bruno (Proceedings of the 17th Annual Conference of the European Association for Machine Translation (EAMT2014), 2014)
We describe fragments of the SMT pipeline at WIPO for German as a source language. Two subsystems are discussed in detail: word decompounding and verb structure pre-reordering. Apart from automatic evaluation results for both subsystems, for the pre-reordering mechanism manual evaluation results are reported.